Ductus arteriosus associated with an anomalous left coronary artery arising from the pulmonary artery: catastrophe after duct ligation. Issue 4 (April 1986) - Ortiz, E; de Leval, M; Somerville, J
Abstract : Chronic left ventricular failure developed two months after ligation of an apparently uncomplicated large ductus arteriosus in a one year old girl. Two years later deterioration had progressed to a terminal stage. An anomalous left coronary artery arising from the pulmonary artery had not been recognised before duct ligation. This anomaly was diagnosed two years after ligation and was then treated by surgical redirection, but the patient died of severe left ventricular dysfunction.